Impact of Short-Term Bhastrika Pranayama on Respiratory Parameters: An Ancient Practice with Contemporary Significance - Singh Bal Baljinder (Physical Education of Students, 2015)
Purpose: The study was conducted to determine the impact of short-term bhastrika pranayama on respiratory parameters. Material : The research was carried out on a sample of 30 university level girls. Experimental group was subjected to 4-week training of bhastrika pranayama. Statistical Analysis: Student t test was utilized for analysis of data. Results : The Mean and Standard Deviation values of Tidal Volume (VT) of pre-test and post-test of experimental group was 389.60 ± 10.25 and 408.40 ± 27.44 respectively. However, the Mean and Standard Deviation values of Tidal Volume of pre-test and post-test of control group were 352.93 ± 8.80 and 351.40 ± 9.83. The t-value in case of experimental group was 2.8976 and for control group it was 1.3580. Conclusions : The significant differences were noted in Tidal Volume, Expiratory Reserve Volume, Inspiratory Reserve Volume, Vital Capacity and Inspiratory Capacity in the experimental group. However, insignificant changes over that 4-week period were noted in the control group.